Aflatoxin producing Aspergillus spp. and aflatoxin levels in stored cassava chips as affected by processing practices - Essono , G.G.; Ayodele, M.; Akoa, A.; Foko, J.; Filtenborg, O.; Olembo, S. (Elsevier, 2009)
Cassava chips (cassava balls, and cassava pellets) are derived cassava products traditionally produced byfarmers in sub-Saharan Africa following fermentation, and drying of fresh roots of cassava, and are widelyconsumed in Cameroon. Once produced, this food commodity can be stored for more than two monthsand contaminated by a wide array of harmful microbes. In order to assess persistence of toxigenic fungiin cassava chips, aflatoxin-producing fungi (Aspergillus flavus, Aspergillus nomius,andAspergillus parasit-icus) and aflatoxins were contrasted at regular intervals in home-stored cassava chips collected in twolocations of southern Cameroon throughout a two-month monitoring period. Three hundred and forty-six isolates of aflatoxin-producing fungi were found to be associated with all samples.A. flavuscontam-inated more samples in both types of chips (267 isolates in 53 samples), followed byA. nomius(58 iso-lates in 15 samples), whereasA. parasiticuswas rarest. A direct competitive Enzyme-linkedimmunosorbent assay (ELISA)-based method was implemented to quantify the content in aflatoxins.Eighteen of the samples contained some aflatoxins at detectable levels whereas 54 did not. The levelsof aflatoxin ranged between 5.2 and 14.5 ppb. The distribution of aflatoxin in positive samples dependedon 8 parameters including pH, moisture content, storage duration, types of chips, level of contaminationby aflatoxin-producing fungi, processing practices and storage facilities. From analysis of variance results,only pH (p< 0.01), duration of storage (p< 0.01), population of aflatoxin-producing species (0.0001) andthe chip type (p< 0.05) were significantly related to aflatoxin in positive samples. A stepwise regressionanalysis (forward selection procedure) indicated that aflatoxin levels were significantly (p< 0.01) corre-lated with processing practices, storage facilities, and storage duration of the chips.